Pengaruh Struktur Modal, Umur Perusahaan dan Komite Audit Terhadap Nilai Perusahaan pada Perusahaan Sektor Infrastruktur yang Terdaftar di Bursa Efek Indonesia - Munadia Sufindra Laely; Ratna Anggraini; Muhammad Yusuf (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to present empirical evidence on the effect of capital structure, company age, and audit committee on company value in infrastructure companies listed on the Indonesia Stock Exchange. Company value in this study is proxied by Price Book Value (PBV). The study was conducted using quantitative methods with secondary data sourced from annual reports. The research population includes infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Through purposive sampling, 147 observation samples were obtained, which were then analyzed using panel data regression with the help of Eviews 13 software. The results showed that company age had a positive effect on company value, while capital structure and audit committees were not proven to have an effect on company value.